The Influence Of Leadership On Organizational Change At Pt Kereta Api Indonesia (Pt Kai) During Ignasius Jonan's Leadership - Ogi Rahamdana; Nuri Aslami (Penerbit Jurnal Indonesia, 2023)
The role of the leader in an organization is very influential on the direction of the organization, this can be seen in PT Kereta Api Indonesia (KAI). Like a vehicle, the leader becomes the person who is responsible for taking full control and becomes the person most responsible for bringing the vehicle to the planned destination. Since Ignasius Jonan's leadership, the face of Indonesian Railways looks brighter and more colorful, Ignasius Jonan changed PT KAI from what was initially not used too often to become a very popular transportation option and is often used by passengers. Upstream to downstream of PT KAI was repaired and renewed by him so that during his leadership period PT KAI became one of the modes of transportation with considerable advantages.